Allylic C–H Alkynylation via Copper-Photocatalyzed Cross-Dehydrogenative Coupling - Almasalma, Ahmad A.; Mejía, Esteban (Synthesis, 2020)
An efficient, novel photocatalyzed allylic-alkynylation methodology via copper-based cross-dehydrogenative coupling (CDC) is described. Different types of 1,4-enyne compounds were synthesized in one step at room temperature using copper(I) terpyridyl complex as photocatalyst/initiator. This procedure is an improvement and to some extent complementary to previously reported thermal CDC methods. Preliminary investigations on the reaction mechanism are also presented.
Keywords: C–C bond; copper catalyst; C–H functionalization; photocatalyst; allylic-alkynylation; 1,4-enyne